Heterodyne dynamic light scattering for the characterization of particle dispersions - Wu, Wenchang; Knoll, Matthias; Giraudet, Cédric; Rausch, Michael Heinrich; Fröba, Andreas Paul (Applied Optics, 2023)
Particle self-diffusivities in unimodal and bimodal aqueous dispersions are characterized by dynamic light scattering (DLS) applying a heterodyne detection scheme. For unimodal dispersions close to infinite dilution, it could be evidenced that pure homodyne conditions cannot be realized, leading to an increasing underestimation of diffusivity with a decreasing concentration. Even for bimodal dispersions and neglecting any local oscillator field, the coherent superposition of scattered light from different particle species hinders a clear assignment of the measured signals and their evaluation for diffusivity. In this case, the impact of a cross term on the determined diffusivities cannot be neglected. The results emphasize that the use of a heterodyne detection scheme in DLS experiments is a key aspect for an accurate determination of particle diffusivities in low-concentrated unimodal and bimodal dispersions.
CRIS-Team Scopus Importer:2023-11-24